Lensing and x-ray mass estimates of clusters (simulations) - Rasia, Elena; Merten, Julian (New journal of physics, 2012)
We present a comparison between weak-lensing and x-ray mass estimates of a sample of numerically simulated clusters. The sample consists of the 20 most massive objects at redshift z = 0.25 and M vir > 5 × 10 14 M ⊙ h −1 . They were found in a cosmological simulation of volume 1 h −3 Gpc 3 , evolved in the framework of a WMAP-7 normalized cosmology. Each cluster has been resimulated at higher resolution and with more complex gas physics. We processed it through Skylens and X-MAS to generate optical and x-ray mock observations along three orthogonal projections. The final sample consists of 60 cluster realizations. The optical simulations include lensing effects on background sources. Standard observational tools and methods of analysis are used to recover the mass profiles of each cluster projection from the mock catalogue. The resulting mass profiles from lensing and x-ray are individually compared to the input mass distributions. Given the size of our sample, we could also investigate the dependence of the results on cluster morphology, environment, temperature inhomogeneity and mass. We confirm previous results showing that lensing masses obtained from the fit of the cluster tangential shear profiles with Navarro-Frenk-White functionals are biased low by ∼5-10% with a large scatter (∼10-25%). We show that scatter could be reduced by optimally selecting clusters either having regular morphology or living in substructure-poor environment. The x-ray masses are biased low by a large amount (∼25-35%), evidencing the presence of both non-thermal sources of pressure in the intra-cluster medium (ICM) and temperature inhomogeneity, but they show a significantly lower scatter than weak-lensing-derived masses. The x-ray mass bias grows from the inner to the outer regions of the clusters. We find that both biases are weakly correlated with the third-order power ratio, while a stronger correlation exists with the centroid shift. Finally, the x-ray bias is strongly connected with temperature inhomogeneities. Comparison with a previous analysis of simulations leads to the conclusion that the values of x-ray mass bias from simulations are still uncertain, showing dependences on the ICM physical treatment and, possibly, on the hydrodynamical scheme adopted.